Auditing principles - Stettler, Howard F. (Englewood Cliffs, N.J. : Prentice-Hall, 1977)
This book gives a detailed information on independent audits, professional responsibilities of the independent auditors and general auditing standards.
Includes index.
ne 27/06/2019
Loans
Keywords: Auditing